TRADISI MERASI DALAM ADAT PERKAWINAN MELAYU RIAU (STUDI ANALISIS TERHADAP PENENTUAN KAFAAH CALON PENGANTIN DI KELURAHAN BAGAN BATU) - Rahmat Pulungan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Kafaah aims to create harmony and balance in marriage. The criteria of kafaah in jurisprudence according to scholarly are nasab, wealth, beauty, diyanah, hirfah and self independence. The problem that occurs is when determining kafaah in Bagan Batu, the Malay community has its own way in the process or determine kafaah; they carry the tradition called merasi to ensure compatibility between their children who will carry out the marriage. The main problem to be answered through this research is to determine how the process of merasi in determinig kafaah conducted by Malay community in Bagan Batu, what is the purpose of this tradition and how the views of Islamic law against the tradition. The purpose of this study: 1). To know the procedures of merasi tradition 2). To find out the purpose of merasi in determining kafaah 3). To find out the views of the Islamic law in the determination of kafaah through merasi process undertaken by the community of Bagan Batu , Bagan Sinembah ,Riau Province. The research is a field research that is descriptive qualitative. In the collection of necessary data, the author uses interview and observation techniques. While in the data analysis techniques, used qualitative method that describes the situation on the ground systematically. The results of this research is merasi tradition that conducted by people in Bagan Batu by combining both the name of the bride, and the progenitor will predict the state of their household after marriage. The way of this merasi may vary according to the progenitor who will perform it. Whereas the purpose of this merasi to reduce the disadvantages and for the achievement of the benefit in marriage. Merasi tradition in determining kafaah that happened inBagan Batu may be accepted and enforced. Because, during the process nothing contrary to Islamic law, also aimed to benefit of the people. In fact, before merasi the progenitor will ask the religious understanding of the bride, and it is also used as a basic foundation for determining the kafaah between the couple Kafaah bertujuan untuk menciptakan keserasian dan keseimbangan dalam perkawinan. Kriteria kafaah dalam fikih menurut jumhur ulama ialah nasab, kekayaan, kecantikan, diyanah, hirfah, dan kemerdekaan diri. Permasalahan yang terjadi adalah saat menentukan kafaah, di Kel. Bagan Batu, para masyarakat Melayu mempunyai proses atau cara tersendiri dalam menentukan kafaah, mereka melaksanakan tradisimerasi untuk memastikan keserasian antara anak mereka yang akan melaksanakan perkawinan. Masalah penelitian ini adalah bagaimana proses merasi dalam menentukan kafaah yang dilakukan masyarakat Melayu di Kel. Bagan Batu, apa tujuan dari tradisimerasi dan bagaimana pandangan hukum Islam terhadap tradisimerasi tersebut. Riau. proses merasi yang dilakukan masyarakat Bagan Batu yaitu dengan cara menggabungkan kedua nama calon mempelai, dan datuk yang bersangkutan akan meramal keadaan rumah tangga mereka setelah menikah. Cara merasi ini beragam metodenya sesuai dengan datuk yang akan mem-faal. Sedangkantujuan dari merasi ini untuk mengurangi kemudharatan dan demi tercapainya kemaslahatan dalam pernikahan. Tradisi merasi dalam penentuan kafaah yang terjadi di Kel. Bagan Batu ini boleh diterima dan diberlakukan. Karena, selama proses merasi tidak ada hal yang bertentangan dengan hukum Islam yang juga menginginkan kemaslahatan umat. Bahkan, sebelum merasi para datuk akan menanyakan pemahaman agama para calon pengantin, dan hal ini juga dijadikan sebai landasan dasar dalam menentukan kafaah antara pasangan tersebut.